MATERNAL RESTRICTIVE DIETS DURING LACTATION IMPAIR GABAERGIC SIGNALING IN THE HYPOTHALAMUS AND MIDBRAIN IN MALE ADULT RATS (Arquivos do Mudi, 2023)
The aim of this work was to evaluate the behavioral parameters and the GABAergic signalingin the hypothalamus, midbrain and medulla. Mothers and litters were distributed into 3groups: Control (CO) fed with standard diet (20% protein), food restriction (FR) withstandard diet limited of 50% of the daily consumption of CO, and low-protein (LP) fed withLP-diet (4% protein). Interventions were carried out from the 1st-14th, and 14 th -21st day oflactation. Offspring of both sexes were evaluated until 120 days old by elevated plus maze(EPM) and open field (OP) test. Male LP rats showed a decrease in the closed arm (CO158±11.51 vs LP 105.5±9.63; s), an increase in the open arm (CO 85.10±8.65 vs LP139.8±12.36; s) time, and in the number of open arm entries (CO 5.25±0.58 vs LP 8.40±0.79;a.u.) compared to the CO. In OP, male LP rats showed an increase in crossings (CO51.94±4.29 vs LP 71±3.41; a.u.) and in the frequency of crossings (CO 51.94±4.29 vs69.25±4.44; a.u.) compared to the CO. Male FR showed a decrease in the expression ofGABA B receptors (CO 100±12.60 vs FR 56.34 v 4.19; % control). In the midbrain, male LPand FR showed a decrease in GAD (CO 100±11.22 vs LP 47.59±6.21 vs FR 74.18±8.82; %control) compared to the CO. In conclusion, maternal protein and caloric restriction duringlactation induces less anxious behavior and increases exploratory activity in males inadulthood, through modulation in GABAergic signaling.